Alzheimer disease associated variants in SORL1 accelerate dementia development in Parkinson disease. (1st May 2018) - Maple-Grødem, Jodi; Chung, Janete; Lunde, Kristin Aaser; Tzoulis, Charalampos; Tysnes, Ole-Bjørn; Pedersen, Kenn Freddy; Alves, Guido
Highlights: SORL1 is a key factor in AD, but a possible role in other dementias is unknown. The common SORL1 A528T variant is associated with increased risk of dementia in PD. SORL1 A528T carriers had a reduced ratio of CSF β-amyloid 42 to p-Tau. AD related disease mechanisms may contribute to dementia in some patients with PD. Abstract: Objective: Dementia in Parkinson disease (PD) is a common occurrence, and shows a marked overlap at a clinical and pathological level with Alzheimer's disease (AD), suggesting they share underlying disease mechanisms. Genetic variants in SORL1 have been identified in patients with AD, but a possible role in other dementias is unknown. The aim of this study was to investigate whether common polymorphisms in SORL1 affect the risk of developing dementia in a population-based cohort of patients with incident PD. Methods: One common, nonsynonymous SORL1 variant (rs2298813; A528T) was identified in whole exome sequencing data from 185 patients with PD from the Norwegian ParkWest study, who had been followed up to the 7-year visit after diagnosis. A528T was tested for association with PD risk, the development of dementia, and in a subset of patients (n = 103) for associations with established AD cerebrospinal fluid (CSF) biomarkers measured at the time of PD diagnosis. Results: We found an association of A528T carrier status with increased risk of developing PD dementia (HR 2.31; 95% CI 1.09–4.90; p = 0.03) compared to non-carriers. Additionally, A528T carrier status was associated with a reduced ratio of CSF β-amyloid 42 to p-Tau (p = 0.014) but no alterations in absolute AD marker levels (all p > 0.05) at the time of PD diagnosis. Conclusion: Our results show the first association of the AD risk factor SORL1 with incident dementia in PD, providing new evidence that AD related disease mechanisms may contribute to dementia in a subset of patients with PD. Finding support for a shared etiology for AD and PD dementia provides new directions for research into treatments for these diseases.